Noise induced energy excitation by a general environment - Villar, Paula Ines (2007)
We analyze the effects that general environments, namely ohmic and non-ohmic, at zero and high temperature induce over a quantum Brownian particle. We state that the evolution of the system can be summarized in terms of two main environmental induced physical phenomena: decoherence and energy activation. In this Letter we show that the latter is a post-decoherence phenomenon. As the energy is an observable, the excitation process is a direct indication of the system-environment entanglement particularly useful at zero temperature. © 2007 Elsevier B.V. All rights reserved.